Monitoring Damage and Air Pollutant Parameters after Forest Fire: A Case Study of Çanakkale Fire - Özer Akyüre (Doğal Afetler ve Çevre Dergisi)
Forests are an indispensable part of the Earth in terms of their biodiversity and contributions. Fires are one of the most important factors affecting forests, which cover one third of our planet. Forest fires are among the most destructive natural disasters on Earth and are also a very important source of gases and aerosols. The monitoring of forest fires is extremely important for disaster monitoring and prevention. Geographic Information Systems (GIS) and remote sensing, which have been widely used in fire monitoring in recent years, are prominent methods in terms of data collection, analysis and interpretation. This study focuses on the analysis of the forest fire that occurred in Çanakkale on August 22, 2023 and lasted for 3 days with the help of Sentinel-2 and 5P remote sensing images and GIS. The results of the analysis showed that the total area affected by the fire was 4191.93 hectares (ha) and covered a wide range of land cover/use classes. In particular, forests and agricultural lands were the most severely affected in this region. The aerosol index and nitrogen dioxide (NO2) air pollution parameters, which indicate the concentration of pollutants emitted into the atmosphere after the fire, were monitored and their concentrations determined from satellite imagery. The highest NO2 concentration recorded was 0.02624702 mol/m² on August 24, the last day of the fire. The total amount of NO2 emitted into the atmosphere for three days was determined to be 0.06020184 mol/m².